Synthetic bacteria for the detection and bioremediation of heavy metals - Thai, Thi Duc; Lim, Wonseop; Na, Dokyun (Frontiers in Bioengineering and Biotechnology, 2023)
Environmental pollution resulting from human activity adversely impacts natural ecosystems. Of many pollutants, toxic heavy metals have been accumulating in diverse environments and causing human health risks and ecological disruption. The remediation of heavy metals from environments has relied mostly on chemical and physical methods for decades, which are costly due to expensive equipment and monitoring systems, consumption of plenty of reagents and energy, and toxic waste product formation and additional requirement for their remediation. Recently, microbial bioremediation has been gaining great interest due to its high efficiency and low cost compared to conventional methods. Despite this, the genetic complexity of microorganisms and the lack of appropriate genetic engineering technologies have dampened the advance of microbial bioremediation. Recently, synthetic biology has addressed the challenges in the construction of bacteria capable of detecting and degrading heavy metals rapidly as well as tolerating high toxic concentrations for better performance. Furthermore, synthetic biology also provides new technologies to meet biosafety regulations since genetically modified microorganisms may disrupt natural ecosystems. Therefore, synthetic biology opened a new avenue for future microbial bioremediation. In this review, microorganisms developed based on synthetic biology technologies to detect and detoxify heavy metals are introduced.